ANALISIS FAKTOR PERTIMBANGAN PEMILIHAN LOKASI USAHA (Kasus Pada Usaha Jasa Fotocopy, Penyiapan Dokumen dan Jasa Khusus Penunjang Kantor Lainnya Di Lingkungan Kampus Universitas Riau Pekanbaru) - Firman Mulyadi; Sri Zuliarni (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
The purpose of this study was to analyze the factors considered in the selection of sites within the campus of the University of Riau Pekanbaru. The research concludes that the result of research conducted to entrepreneurs photocopy services, document preparation and specialized services supporting other offices on campus at the University of Riau Pekanbaru access factors, visibility, traffic (traffic), parking lot, and competitive environment of significant value.Keywords: business location, business copy services, campus environment.